Integrating melt electrospinning writing and microfluidics to engineer a human cardiac microenvironment for high-fidelity drug screening - Yu-hong Wang; Ting-ting Liu; Yan-ping Guo; Shuo-ji Zhu; Zi-ming Liao; Jia-mei Song; Xi-ming Zhu; Jia-liang Liang; Moussa Ide Nasser; Nan-bo Liu; De-hua Chang; Ping Zhu; et al. (Bioactive Materials)
The preclinical evaluation of drug-induced cardiotoxicity is critical for developing novel drug, helping to avoid drug wastage and post-marketing withdrawal. Although human induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) and the engineered heart organoid have been used for drug screening and mimicking disease models, they are always limited by the immaturity and lack of functionality of the cardiomyocytes. In this study, we constructed a Cardiomyocytes-on-a-Chip (CoC) that combines micro-grooves (MGs) and circulating mechanical stimulation to recapitulate the well-organized structure and stable beating of myocardial tissue. The phenotypic changes and maturation of CMs cultured on the CoC have been verified and can be used for the evaluation of cardiotoxicity and cardioprotective drug responses. Taken together, these results highlight the ability of our myocardial microarray platform to accurately reflect clinical behaviour, underscoring its potential as a powerful pre-clinical tool for assessing drug response and toxicity.